Financial Liberalization and Productivity among Commercial Banks and Regional Development Banks in Indonesia - Zuberi, Ma'mun (2003)
Since the government of Indonesia liberalized the financial system in 1988, the number of banks and branch office networks grew rapidly, new financial products and services were introduced, electronics banking were developed, and 24-hour bank services were accessible. The financial liberalization has successfully brought about the financial market to be more competitive, which in turn exerts banks to improve their performance. Prior to financial liberalization, state owned commercial banks and state owned regional development banks were both accorded certain privileges by the Bank of Indonesia (SI). Among the privileges were extensive branch networks, access to Bank Indonesia (BI) regarding to liquidity credit at subsidized rate, and the exclusive right to receive public enterprise deposits. These privileges were not extended to other group of banks even though they operate in the same market. Therefore, the liberalization of the financial system has mostly affected the state owned commercial banks and the state owned regional development banks compared to other groups of banks.The objective of this study is to investigate the overall productivity of the state owned commercial banks and the state owned regional development banks in response to the financial liberalization over the period of 1987 to 1996. The research evaluates banks' technical efficiency, isolates the contributions of each component of productivity stemming from efficiency change, technical change, and return to scale of technology. For that purpose, this study used data envelopment analysis (DEA) to estimate the technical efficiency and Generalized Malmquist Productivity Index (GMPI) to measure productivity. The result of study shows that the overall productivity of both state owned commercial banks and state owned regional development banks declined following financial liberalization. The state of decline in productivity of state owned commercial banks is mainly associated with the decline of technical efficiency change. On the other hand, state of decline in productivity of state owned regional development banks is particularly associated with technical regress. However, there is no clear deterioration pattern of productivity amongst the state owned regional development banks. In terms of efficiency, this group of banks experienced improvement following financial liberalization. In general, the result weakly supports that financial liberalization brings about improvement of the performance of state owned commercial banks and state owned regional development banks. However, the outcomes of financial liberalization could possibly be better if its implementation was sequenced after the restructuring of the financial systems such as by enforcing prudential measures (capital adequacy ratio, CAR).